Entrepreneurship in crisis: the determinants of syrian students’ entrepreneurial intentions - Mouselli, Sulaiman; Khalifa, Bayan (Business, Management and Economics Engineering, 2017)
This study aims at investigating the factors that affect the entrepreneurial intentions of university students in Syria. The impact of three groups of factors was investigated, demographic, personal, and external factors. The questionnaire survey method was applied. Data was collected from two major universities in Syria: Damascus University and Arab International University and two faculties: Business and Economics, and Informatics and Communication Engineering. We analyze 183 responses from the above-mentioned faculties to understand whether differences exist in entrepreneurial intentions between students from different universities and faculties. Also, we use ordinary least squares to uncover the determinants of entrepreneurial intentions for those students. The results show higher entrepreneurial intentions for Informatics and Communication Engineering and for male students. Moreover, self-efficacy, information and communication, institutional environment come to have positive and significant impacts on entrepreneurial intentions. We recommend that more polices should be directed towards developing female entrepreneurial intents. Also, entrepreneurship training courses should be offered to Informatics and Communication Engineering to enable them turn their intentions into projects. Furthermore, universities should consider establishing entrepreneurship centers, incubators and science parks that foster innovative ideas and support start-ups.